La aplicación del principio de igualdad y no discriminación a los trabajadores migratorios. (2012)
The principle of equality and non-discrimination is considered one of the main pillars and inspiring in most international instruments on human rights protection. This concept implies that all persons subject to the jurisdiction of a State may enjoy the same rights enshrined in these texts. Nevertheless; the application of that principle to foreign persons poses limitations that are authorized by the International Law of Human Rights; which does not involve discriminatory treatment; but is defined as a distinction or difference in treatment provided each time certain parameters are defined by existing universal jurisprudence